2015
DOI: 10.1186/s13104-015-1519-8
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of non-adherence to antihypertensive medication in Kinshasa, Democratic Republic of Congo: a cross-sectional study

Abstract: BackgroundHypertension remains a public health challenge worldwide. In the Democratic Republic of Congo, its prevalence has increased in the past three decades. Higher prevalence of poor blood pressure control and an increasing number of reported cases of complications due to hypertension have also been observed. It is well established that non-adherence to antihypertensive medication contributes to poor control of blood pressure. The aim of this study is to measure non-adherence to antihypertensive medication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
37
5
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 29 publications
14
37
5
6
Order By: Relevance
“…The low prevalence of other comorbidities in this study could be due to low availability of diagnostic materials and laboratory facilities. The level of comorbidity in our finding is also lower than the findings in Congo (53.9%) [34] which may be related to older age of participants in Congo, the difference in early identification and diagnosis of comorbidities or the difference in life style factors between ours and the Congo population.…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…The low prevalence of other comorbidities in this study could be due to low availability of diagnostic materials and laboratory facilities. The level of comorbidity in our finding is also lower than the findings in Congo (53.9%) [34] which may be related to older age of participants in Congo, the difference in early identification and diagnosis of comorbidities or the difference in life style factors between ours and the Congo population.…”
Section: Discussioncontrasting
confidence: 80%
“…In our study, we excluded patients with depression and other psychiatric disorders. The level of adherence in our study is also higher than the finding in Congo (45.8%) [34]. This noted difference in adherence between ours and Congo may be explained by the difference in socio-demographic characteristics.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Hasil ini sejalan dengan penelitian yang dilakukan oleh Lulebo, 22 yang menyatakan bahwa tidak terdapat korelasi antara lamanya menderita suatu penyakit dengan kepatuhan seseorang. Pada umumnya semakin lama orang menderita suatu penyakit maka ia akan semakin paham terhadap penyakit yang dideritanya, namun hasil yang berbeda juga ditemukan, yaitu semakin lama durasi seseorang menderita suatu penyakit maka akan menjadi faktor pemicu seseorang menjadi bosan terhadap pengobatan sehingga menurunkan kepatuhan dalam menjalani terapi.…”
Section: Pembahasanunclassified
“…Indeed, it is surprising that knowledge of hypertensive medicines and the complications of hypertension had no effect on adherence considering results of prior SSA studies. A study assessing adherence to anti-hypertensive therapy among 395 patients in the Democratic Republic of Congo found that poor knowledge of complications and a lack of education to hypertensive patients was significantly associated with nonadherence [10], while in Ethiopia and Algeria, a positive association has been reported between knowledge about hypertension, its treatment and complications, and good adherence [11,12]. Furthermore, In Lesotho and Zimbabwe, inadequate knowledge of hypertension was significantly associated with uncontrolled hypertension [13,14].…”
mentioning
confidence: 99%